Kawasaki disease: A case report - Ojha, AR; Nepal, A; Acharya, R; Shakya, KN (Journal of Kathmandu Medical College, 2012)
Kawasaki disease is a vasculitis of medium sized arteries which is diagnosed by exclusion and by use of diagnostic criteria. It needs a high index of suspicion to diagnose and should be suspected in any child with history of fever for more than a week with rash and lymphadenopathy. Such patients should be treated with intravenous immunoglobulin and Aspirin to prevent complications. Here we report a case of Kawasaki Disease who presented with prolonged fever, rash and lymphadenopathy and made an uneventful recovery. DOI: http://dx.doi.org/10.3126/jkmc.v1i1.7252 Journal of Kathmandu Medical College, Vol. 1, No. 1, Issue 1, Jul.-Sep., 2012 pp.26-28